Blueberry polyphenols extract as a potential prebiotic with anti-obesity effects on C57BL/6 J mice by modulating the gut microbiota - Jiao, Xinyao; Wang, Yuehua; Lin, Yang; Lang, Yuxi; Li, Enhui; Zhang, Xiuyan; Zhang, Qi; Feng, Ying; Meng, Xianjun; Li, Bin (The Journal of nutritional biochemistry, 2019)
Polyphenols are known for their various health benefits. Blueberries are dietary sources of polyphenols with reported health benefits. However, the role of blueberry polyphenols in alleviating obesity is not completely understood. This study investigated the potential positive effect of blueberry polyphenol extract (PPE) on high-fat diet (HFD)-induced obesity in C57BL/6 J mice by modulation of the gut microbiota. Four-week-old C57BL/6 J mice were fed a normal-fat diet or HFD with or without PPE or Orlistat for 12 weeks. Mice fed HFD exhibited increased body weight and adipose tissue weight and disordered lipid metabolism. In contrast, PPE inhibited body weight gain and returned lipid metabolism to normal. Furthermore, 16S rRNA gene sequencing of the fecal microbiota suggested that PPE changed the composition of the gut microbiota in C57BL/6 J mice and modulated specific bacteria such as Proteobacteria, Deferribacteres, Actinobacteria, Bifidobacterium, Desulfovibrio, Adlercreutzia, Helicobacter, Flexispira, and Prevotella. Orlistat also improved obesity and metabolic alterations of HFD mice and modulated the composition of the gut microbiota. Our findings suggest that PPE, as a potential prebiotic agent, influences the gut microbiota to positively affect HFD-induced obesity in C57BL/6 J mice. [Display omitted]